¿Chancón or empollón?, trome or genius?...: the Peruvian Spanish and the Spanish of Spain - Ramírez García, Jessica (2021)
In the Spanish-speaking world, in many cases, there is variation between the lexicon used in the Americas and the lexicon used in Spain. The same occurs among the different countries that make up the Americas, including Peru, for example. Peruvian Spanish has its own lexical repertoire, Peruanismos [Peruvian expressions], which varies from the vocabulary used in Spain and from the rest of the Americas. The aim of this study is, on the one hand, to compare a set of Peruvian words with an equivalent lexical repertoire of the Spanish variety; and, on the other hand, to confirm the current use of these Peruvian expressions, for which purpose the Corpus del Español del Siglo XXI (CORPES XXI) has been consulted. The results obtained confirm that there is a lexical-morphological variation between the Spanish from Peru and that from Spain, as well as the survival of most of the Peruvian expressions collected in this research.